Pengaruh Struktur Aktiva, Ukuran Perusahaan Dan Growth Opportunity Terhadap Struktur Modal Dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Perbankan Yang Terdaftar Di Bei Tahun 2020-2022 - Dewanti, Anya Reza Ayu (Jurnal Manajerial Bisnis, 2024)
This study aims to examine the effect of Asset Structure Policy, Firm Size and Growth Opportunity on Capital Structure with Profitability as a Moderating Variable. This research uses quantitative methods. The population used in this study uses banking companies listed on the Indonesia Stock Exchange for the 2020-2022 period using a sampling technique, namely purposive sampling of 69 samples based on predetermined criteria. The variables examined in this study are Asset Structure, Firm Size and Growth Opportunity which are independent variables, Capital Structure as the dependent variable and Profitability as a moderating variable. The research data were analyzed using Moderated Regression Analysis (MRA) using the SPSS Version 26 analysis tool. The results showed that 1) Asset Structure has a positive effect on Capital Structure, 2) Firm Size has a positive effect on Capital Structure, 3) Growth Opportunity has a positive effect on Capital Structure, 4) Asset Structure has no effect on Capital Structure with Profitability as a moderating variable and has negative direction, 5) Firm size has a positive effect on capital structure with profitability as a moderating variable, 6) Growth Opportunity has no effect on capital structure with profitability as a moderating variable but has a positive direction.